PENINGKATAN PRODUKTIVITAS KULTUR STATIS BRACHIONUSPIICATILIS MUELLER, 1786 DENGAN OPTIMASI JENIS DAN KONSENTRASI PAKAN ALAMI - Noerdjito, Diah Radini; Santika, Gede (Perhimpunan Biologi Indonesia, 2006)
ABSTRACTImprovement of Bracirwnuspficatifis Mueller 1786 Static Culture Productivity byOptimization of Food vpe and Food Concentration. A study to optimize the standardculture procedure by optimization of feeding regime (selection of the best type ofmicroalgae and its concentration used for diet of Brachionus plicatiliz diet) wasconducted in order to support more stable and higher yield production of B. plicatilisculture. A serial experiment was done in two consecutive stages. On each stage, B.plicatilis zooplanktons were cultured in batch system of 30 x 30 x 50 cm3 aquarium,initial density of 10 ind./mL, and constant aeration rate of 200 mLIminute. The density,egg ratio, water quality parameters of the culture (dissolved oxygen, pH, ammoniumlevel, nitrite level, nitrate level) were measured daily. On the first experiment, B. plicatiliscultures were fed on lo6 cells/mL Chlorella sp., Nannochloropsis sp., Tetraselmis sp.,and a combination of those three micro-algae. The results showed that optimum culturedensity was obtained in the culture fed on Nannochloropsis sp. (68*2) indImL on day 5of culture period and the density was significantly different from the other treatments(pc0.05). On the second stage, B. plicatilis cultures were fed on Nannochloropsis sp. infour different concentrations: 1 OS, 1 06, 1 07, and 1 08cells/mL. Optimum culture density(407k9) ind./mL was obtained in the culture fed on 1O7ce1ls/mL Nannochloropsis sp. onday 7 of culture period and the density was significantly different from the other treatments(p<O.O5). It can be concluded that the optimum culture condition (optimum density andmore stable water quality parameter such as NH;' and NO2 of B. plicatilis batch culturescan be obtained by optimization of feeding regime using 1 O7 cells/mL NannochloropsisSP .Key words: Brachionus plicatilis, Nannocloropsis sp., Tetraselmis sp., Chlorella sp.,microalgae concentration, water quality, productivity.